The Efforts of Sabhara’s Patrolic Unit in Prevention of Vehicles Thievery - Teguh Adjisaka (Advances in Police Science Research Journal, 2021)
Motor vehicle theft is a crime that is quite common in Indonesia. This study describes the situation and conditions in the jurisdiction of the West Lombok Police, West Nusa Tenggara Province related to motor vehicle theft. The purpose of this research is to describe how the Sabhara Unit patrol efforts in preventing motor vehicle theft in the jurisdiction of the West Lombok Police. Motor vehicle theft crime prevention efforts have been implemented with the hope that the crime rate of motor vehicle theft can decrease from the previous year. The Sabhara Patrol is described as a preventive operational activity which is still effectively implemented, especially in the context of preventing motor vehicle theft crimes in the jurisdiction of the West Lombok Police. Prevention efforts are carried out in accordance with the rules stated in Perkabaharkam No.1 / 2017. As an analysis to discuss this research, Steven Lab’s crime prevention theory, George R Terry's management theory, Harold Lasswell’s comunication theory and the patrol concept are used. The approach used in this study is a qualitative approach. Data collection was carried out through interview techniques, document study, and observation. Meanwhile, the report preparation uses data reduction analysis techniques, data presentation, and verification. Based on the discussion of the results of the study, it was concluded that the obstacles faced by the West Lombok Police in preventing motor vehicle theft were internal and external factors. From internal factors, among others, the lack of quantity and quality of personnel, and the lack of budget from the department. Meanwhile, external factors include the condition of the community and geographical conditions in West Lombok Regency.